1995
DOI: 10.2527/1995.7319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary virginiamycin on performance and liver abscess incidence in feedlot cattle.

Abstract: The effects of dietary virginiamycin level on performance and liver abscesses in feedlot cattle were evaluated in seven dose-response studies. Steers and heifers were fed finishing diets ranging in energy content from 1.34 to 1.51 Mcal of NEg/kg of DM. In all studies, virginiamycin added to the diet improved average daily gain and(or) feed conversion, with no substantial effect on dry matter intake. Pooled analyses of four studies providing virginiamycin at 11.0, 19.3, and 27.6 mg/kg of DM in the complete diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0
16

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 18 publications
8
68
0
16
Order By: Relevance
“…As previously mentioned, this may have occurred due to changes in ruminal fermentation promoted by virginiamycin supplementation. These results are similar to others reported in the literature, in which estimated NE m and NE g of the diets were higher for feedlot beef cattle supplemented with virginiamycin when compared with control animals (Rogers et al, 1995;Salinas-Chavira et al, 2009).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…As previously mentioned, this may have occurred due to changes in ruminal fermentation promoted by virginiamycin supplementation. These results are similar to others reported in the literature, in which estimated NE m and NE g of the diets were higher for feedlot beef cattle supplemented with virginiamycin when compared with control animals (Rogers et al, 1995;Salinas-Chavira et al, 2009).…”
Section: Resultssupporting
confidence: 82%
“…The isolated utilization of ionophore, like monensin or salinomycin, or non-ionophore antibiotics, such as virginiamycin, as growth promoter feed additives has been thoroughly investigated. The results are consistent in demonstrating improvements on animal performance (Rogers et al, 1995;Zinn, 1986). Moreover, Silva et al (2004) suggested that virginiamycin and ionophore may have an additive effect on growth performance when used in combination, but with no substantial effects on carcass characteristics.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Este antibiótico não ionóforo atua por meio de ligação com os ribossomos, inibindo a síntese de proteína de alguns microrganismos (ROGERS et al, 1995).…”
Section: Introductionunclassified